Integration of Local Wisdom in Digital Parenting Practices in Early Childhood: A Case Study of the Community of Long Nyelong Village, Samarinda - Ratna; Vivi Irzalinda (Universitas Lancang Kuning, 2024)
Effective digital parenting practices ideally balance the utilization of digital technology with the preservation of local cultural values. However, in areas with strong local wisdom such as Long Nyelong Village, Samarinda, the integration of digital parenting practices and traditional values remains a challenge. This study aims to analyze the integration of local wisdom in digital parenting practices for early childhood in Long Nyelong Village. The research employs a qualitative approach with a case study method. Data were collected through in-depth interviews, non-participant observation, and document analysis. Research subjects were selected using purposive sampling technique, involving parents with children aged 2-6 years who have access to digital technology and still adhere to local wisdom values. The results indicate that the Long Nyelong community has successfully adapted parental mediation strategies while maintaining traditional values. Parents have created unique forms of digital parenting, such as